Pediatric gastric ganglioneuroma presenting as anemia - Katrina M. Morgan; Philip A. Erwin; Summer N. Rochester; Cady F. Williams; Robert L. Gates (Elsevier, 2018)
Primary gastric masses are rare in childhood, and a gastric ganglioneuroma has not been reported in the pediatric population. In this report, we describe a 12-year-old female who presented with iron deficiency anemia and melena. Endoscopy was performed to elucidate the source of her symptoms, and revealed a gastric mass with overlying ulceration. Following resection and pathologic examination, the mass was diagnosed as a solitary polypoid ganglioneuroma. A solitary polypoid ganglioneuroma is an uncommon, benign tumor of neural crest cell origin. They are most often asymptomatic and found incidentally, but can present with rectal bleeding, obstruction, pain, and changes in bowel function. Complete resection is the therapy of choice to prevent progression of symptoms or rare transformation into a malignant neuroblastic tumor, like neuroblastoma. As of the patient's last post-operative appointment, she was healthy with resolution of her anemia. Keywords: Ganglioneuroma, Pediatric, Gastric mass, Anemia, Neuroblastic tumor